Estuarine morphodynamics and development modified by floodplain formation - M. G. Kleinhans; L. Roelofs; S. A. H. Weisscher; I. R. Lokhorst; I. R. Lokhorst; L. Braat; L. Braat (Earth Surface Dynamics, 2022)
Rivers and estuaries are flanked by floodplains built by mud and vegetation. Floodplains affect channel dynamics and the overall system's pattern through apparent cohesion in the channel banks and through filling of accommodation space and hydraulic resistance. For rivers, effects of mud, vegetation and the combination are thought to stabilise the banks and narrow the channel. However, the thinness of estuarine floodplain, comprised of salt marsh and mudflats, compared to channel depth raises questions about the possible effects of floodplain as constraints on estuary dimensions. To test these effects, we created three estuaries in a tidal flume: one with recruitment events of two live vegetation species, one with mud and a control with neither. Both vegetation and mud reduced channel migration and bank erosion and stabilised channels and bars. Effects of vegetation include local flow velocity reduction and concentration of flow into the channels, while flow velocities remained higher over mudflats. On the other hand, the lower reach of the muddy estuary showed more reduced channel migration than the vegetated estuary. The main system-wide effect of mudflats and salt marsh is to reduce the tidal prism over time from upstream to downstream. The landward reach of the estuary narrows and fills progressively, particularly for the muddy estuary, which effectively shortens the tidally influenced reach and also reduces the tidal energy in the seaward reach and mouth area. As such, estuaries with sufficient sediment supply are limited in size by tidal prism reduction through floodplain formation.